Parametric prediction model and periodic fluctuation interpretation of unidirectional CFRP edge milling force. (1st May 2022) - Wang, Chenxi; Zhang, Xingwu; Zhai, Zhi; Chen, Xuefeng
Highlights: An analytical parametric model based on the energy balance for machining force prediction is proposed in unidirectional CFRP edge milling. The relation between feed per tooth and the representative volume element (RVE) is analyzed to interpret the milling force fluctuation phenomenon. The numerical simulation for CFRP milling is also implemented for verification of the fluctuation phenomenon. The effect of strain rate on material parameters (such as the engineering moduli and the dominated strengths) is taken into account. The proposed parametric model is validated by milling tests, where the frequency response functions are measured by impact tests for milling force compensation. Abstract: With the the excellent material properties, carbon fiber reinforced polymer (CFRP) composites have been widely accepted in many fields. Edge milling is indispensable for final shape and assembly requirements. However, it's difficult to predict the machining forces due to the anisotropy and inhomogeneity of CFRP. In order to solve this problem, this paper proposed an analytical parametric model for machining force prediction based on the energy balance in unidirectional CFRP edge milling. The involved energies can be divided into five categories: energy consumed for formation of two new surfaces, friction energy at the tool-chip interface, fracture energy for chip formation, energy consumption for subsurface damage and the kinetic energy of flying chip. Experimental results show that the peak of the edge milling force fluctuates periodically. The relation between feed per tooth and the representative volume element (RVE) is analyzed to interpret the fluctuation phenomenon. In addition, the numerical simulation for CFRP milling is also implemented for verification of the fluctuation phenomenon. In calculation, the effect of strain rate on material parameters (such as the engineering moduli and the dominated strengths) is taken into account. In milling tests, in order to obtain the actual forces, the frequency response functions (FRF) are measured by impact tests for milling force compensation. Finally, the predicted milling forces have a good agreement with experimental observations.